THE SECOND YEAR SENIOR HIGH SCHOOL STUDENTS' GRAMMATICAL DIFFICULTIES IN PRESENTING SPOKEN EXPOSITION TEXT - ANISA WAHYUNI; RATMANIDA RATMANIDA; AN FAUZIA ROZANI SYAFEI (Journal of English Language Teaching, 2018)
This research aimed to describe students difficulties in presenting spoken exposition text, limited to the use of simple present tense. This research was a descriptive research, conducted in May-June 2017 at MAN 2 Padang. The population was Grade XI of Science program students of MAN 2 Padang. The sample was 38 students chosen by using stratified random sampling method. The research data was the clauses with grammatical mistakes found in the transcript of students speaking, obtained by a speaking test. The result of the research showed that the most frequent difficulties of verbal clauses using simple present tense were subject-verb agreement (51%) and the use of auxiliary verb (18%). The most frequent difficulties of nominal clauses using simple present tense were no verb (71%) and no subject (13%).